Evolutionary insights into sequence modifications governing chitin recognition and chitinase inactivity in YKL-40 (HC-gp39, CHI3L1) - Suzuki, Keita; Okawa, Kazuaki; Ohkura, Masashi; Kanaizumi, Tomoki; Kobayashi, Takaki; Takahashi, Koro; Takei, Hiromu; Otsuka, Momo; Tabata, Eri; Bauer, Peter O; Oyama, Fumitaka (The Journal of biological chemistry, 2024)
YKL-40, also known as human cartilage glycoprotein-39 (HC-gp39) or CHI3L1, shares structural similarities with chitotriosidase (CHIT1), an active chitinase, but lacks chitinase activity. Despite being a biomarker for inflammatory disorders and cancer, the reasons for YKL-40's inert chitinase function have remained elusive. This study reveals that the loss of chitinase activity in YKL-40 has risen from multiple sequence modifications influencing its chitin affinity. Contrary to the common belief associating the lack of chitinase activity with amino acid substitutions in the catalytic motif, attempts to activate YKL-40 by creating two amino acid mutations in the catalytic motif (MT-YKL-40) proved ineffective. Subsequent exploration that included creating chimeras of MT-YKL-40 and CHIT1 catalytic domains (CatDs) identified key exons responsible for YKL-40 inactivation. Introducing YKL-40 exons 3, 6, or 8 into CHIT1 CatD resulted in chitinase inactivation. Conversely, incorporating CHIT1 exons 3, 6, and 8 into MT-YKL-40 led to its activation. Our recombinant proteins exhibited properly formed disulfide bonds, affirming a defined structure in active molecules. Biochemical and evolutionary analysis indicated that the reduced chitinase activity of MT-YKL-40 correlates with specific amino acids in exon 3. M61I and T69W substitutions in CHIT1 CatD diminished chitinase activity and increased chitin binding. Conversely, substituting I61 with M and W69 with T in MT-YKL-40 triggered chitinase activity while reducing the chitin-binding activity. Thus, W69 plays a crucial role in a unique subsite within YKL-40. These findings emphasize that YKL-40, though retaining the structural framework of a mammalian chitinase, has evolved to recognize chitin while surrendering chitinase activity.
Keywords: Chitin; molekulární evoluce; Catalytic Domain; Amino Acid Substitution; exony; Humans; Evolution, Molecular; Exons; hexosaminidasy; lidé; Hexosaminidases; Amino Acid Sequence; protein CHI3L1; substituce aminokyselin; katalytická doména; Chitinase-3-Like Protein 1; chitinasy; Chitinases; chitin; sekvence aminokyselin